Construction of optical system for an atomic clock-beyond atomic fountain - Wang, Xiumei; He, Jin; Wang, Yifei; Wang, Yunjia; Wang, Wenming; Wang, Weili; Li, Shiguang; Zhu, Xi; Liu, Guodong; Liu, Shuo; Wang, Ye; Wang, Liang; et al. (Frontiers in Physics, 2022)
We demonstrate the construction of the optical system in the atomic clock-beyond atomic fountain based on 87Rb atom. The optical system includes a high-stability laser system and an optical lattice. The high-stability laser system with the new scheme of frequency locking and shift is introduced in detail, which is an important laser source for laser cooling. The optimized frequency and intensity stability are achieved to 4 × 10–14τ−1/2 (τ is the averaging time) and 4 × 10–5τ−1/2, respectively, which are highly stable. On the basis of the conventional atomic fountain clock, the optical lattice is specially investigated along the direction of gravity and its characteristics are studied systematically. For the optimized and novel exploration, we predict the achievable stability of 3.6×10−14τ−1/2 and it has the potential to be improved to 3.6×10−15τ−1/2. The realizability of the construction due to the stabilized laser and optical lattice makes the beyond fountain promising candidate for the next-generation high performance microwave atomic clock.